The combined influence of chronic kidney disease and peripheral artery disease on long-term all-cause and cardio-cerebrovascular disease mortality among middle-aged and elderly individuals: A nationwide cohort study - Yan-Fang Zhang; Ze-Huang He; Xiao-Feng Zhu; Guo-Jun Ge; Xuan Li (PLoS ONE, 2025)
Background The National Health and Nutrition Examination Survey (NHANES) is a nationwide program that evaluates the health and nutritional status of individuals in the United States. Chronic kidney disease (CKD) and peripheral artery disease (PAD) are major contributors to morbidity and mortality, yet their combined impact on mortality outcomes remains uncertain. Methods We analyzed data from NHANES 1999–2004, focusing on individuals aged 40 years and older. CKD was defined by urinary albumin to creatinine ratio (UACR) >30 mg/g or estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m2, while PAD was determined by an ankle-brachial pressure index (ABI) ≤0.90. Mortality outcomes, including all-cause and cardio-cerebrovascular disease (CCD) mortality, were assessed via linkage to the National Death Index through December 2019. Results Among 7,243 participants, 2,848 all-cause deaths and 921 CCD deaths occurred during a median follow-up of 16.92 years. Participants with concomitant CKD and PAD had higher risks of mortality than those with neither condition or with only one condition. For all-cause mortality, individuals with both CKD and PAD showed the highest risk (adjusted hazard ratio [HR]=3.25, 95% CI: 2.55–4.14, P < 0.001). For CCD mortality, the concurrent group likewise had the greatest risk (adjusted HR = 4.76, 95% CI: 3.41–6.63, P < 0.001). Conclusion Coexisting CKD and PAD are associated with substantially elevated risks of all-cause and CCD mortality among middle-aged and older adults. These findings highlight the need for comprehensive, integrated management strategies for individuals with both conditions to mitigate mortality risk.